Thermal field of deposited coverings - Jurov, V.M.; Laurinas, V.Ch. (KSU publ., 2013)
In work formation of ionic-plasma coverings when film growth is defined by conditions on mobile border of section of phases is considered. The analytical decision of the general problem with any boundary conditions is received. For homogeneous boundary conditions which are closest to technology of drawing of ionicplasma coverings, the formula for a temperature field of deposited coverings is received. The carried out analysis has shown, that at formation of an ionic-plasma covering there is a wave structure. Comparison with results of measurement of microhardness of a covering along the sample has proved theoretical model. The received result can be used for perfection of technology of drawing of ionic-plasma coverings of a various functional purpose.
Keywords: plasma; covering; thermal field; mobile border of section of phases; wave structure; microhardness